(untitled) (Revista de Artes Marciales Asiáticas, 2021)
This study aimed to investigate the effect of weigh-in time on hydration status and acute weight gain (AWG). Twenty-seven men judo athletes and 23 men wrestlers voluntarily participated in this study. Body mass and urine specific gravity (USG) of the athletes were measured just before official weigh-in and competition. Two-way analysis of variance (split-plot ANOVA) with repeated measurements (time x sport) were used to determine differences in AWG and USG between groups and measurement times. In case of significant difference between sports, t-tests were applied. There was a significant main effect of time (p<0.01, ES=0.25) on USG. A significant difference was found in USG between official weigh-in and start of the competition in wrestlers (p<0.01) but not in judo athletes. There was significant difference in AWG and AWG% between sports (p<0.01). Moreover, most of the athletes presented high level of dehydration before both official weigh-in and competition. In conclusion, judo athletes could not rehydrate as much as wrestlers despite 15h of recovery. It can be suggested that the period between official weigh-in and competition would be shortened to prevent non-optimal hydration status and rapid weight gain, with caution to allow sufficient recovery period.